(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines modern mechanisms for state regulation of the money supply in the country. An analysis is provided of the main instruments of monetary policy, along with their influence on economic stability and the dynamics of inflationary processes. Special attention is paid to the role of the central bank and methods of influencing the financial system’s liquidity with the aim of maintaining a balance between stimulating economic growth and controlling inflation.